The efficacy of indicated prevention of depression: A review. - Vázquez, Fernando; Blanco, Vanessa; Torres, Ángela; Otero, Patricia; Hermida, Elisabet (Anales de Psicología / Annals of Psychology, 2013)
This paper reviewed the research on the effectiveness of psychological and psychoeducational interventions to prevent depression in subjects with symptoms of depression, but that did not meet criteria for a current major depressive episode (indicated prevention). Forty-two randomized controlled trials, evaluating thirty-six preventive programs identified through the Medline, PsycINFO, ERIC and EMBASE databases and the Cochrane Collaboration of Depression, Anxiety and Neurosis Group Controlled Trials Register, in Spanish and English, between 1990 and 2013, were selected. Most indicated prevention programs showed positive effects on depressive symptoms. However, they have been found to produce small effect sizes, and many of them had no effect on the incidence of depressive disorders. In addition, many of these studies had methodological weaknesses. Current findings support the need to develop preventive interventions following one model of indicated prevention, and assessing their efficacy through randomized controlled trials with adequate methodological quality.